Beyond school gates: the role of motivation in music learning on elementary school students’ daily music listening behaviors - Yuki Harada; Saho Takeishi (Frontiers in Psychology)
BackgroundResearch in music psychology suggests that attentive music listening cultivates deeper understanding and creativity. However, many children engage with music primarily in informal settings, so a high level of motivation for formal music learning does not necessarily translate into everyday music-listening behavior. This study examined whether motivation for formal music learning predicts students’ out-of-school music-listening behaviors, even after accounting for their motivation for informal music engagement.MethodsParticipants were 1,382 elementary school students (Grades 4–6) in Japan. First, we developed a new scale to measure expectancy belief for formal music learning across five domains: instrumental performance, singing, composing, listening, and studying musical terminology. Second, we conducted a main study using structural equation modeling to test whether motivation for formal and informal music engagement (each with expectancy belief and task value) would explain two type of everyday music-listening behaviors: intention to access music and attention to musical elements.ResultsFactor and correlation analysis supported the validity of the new expectancy belief scale. Structural equation modeling showed that while the intention to access music was primarily predicted by motivation for informal music engagement, the attention to musical elements was significantly explained by both informal and formal music motivation. Notably, an interaction emerged in which higher expectancy beliefs reinforced the positive effect of task value on attention to musical elements.DiscussionAlthough motivation for formal music learning showed little association with the intention to access music, its significant association with attention to musical elements suggests that school music education and everyday music listening are not entirely disconnected. Motivation for formal music learning may foster more analytical engagement with music in daily life, supporting broader educational goals of musical understanding and creativity.